Online teaching of romance literature and culture during pandemic - Pavle Sekeruš; Bojana Kovačević; Tanja Jevremov (University of Belgrade, Teacher Education Faculty, 2021)
The World Health Organization declared a coronavirus pandemic on March 11, 2020. Measures taken to prevent the spread of the virus have dramatically changed the functioning of schools and forced teachers and students around the globe to adapt quickly to virtual teaching with which many had no previous experience. While exploring the circumstances in which the online teaching of French and Hispanic literature and culture took place at the Department of Romance Studies at the Faculty of Philosophy, University of Novi Sad (FFUNS), we faced a series of questions that needed to be addressed: how students master new technologies, what is their attitude towards online teaching, what shortcomings did they notice, and what made it easier for them to learn the subject content. The first part of the paper provides an overview of the selected literature on virtual teaching published in French, Spanish, English, and Serbian, while the second part presents an analysis of a survey conducted among the students of the Department of Romance Studies at FFUNS who attended classes during the pandemic. The obtained results, valuable both for the improvement of online literature and culture classes and for virtual teaching in general, indicated that the majority of the surveyed students have a negative or moderately negative attitude towards online teaching, while more than a half rated online teaching as equally or less difficult as face-to-face teaching, emphasizing a more flexible organization of time and greater opportunities for using the multimedia content in literature and culture classes. Based on the students' answers, it turns out that the achieved results measured by the number of the passed exams and grades do not differ significantly in relation to the lectures in the classroom.